Bilingualism: An Asset or a Burden? - Dewi, Ienneke I. (Bina Nusantara University, 2008)
The article shows literary scholar opinion whether bilingualism is an asset or burden. The literary scholars see it from many aspects such as neuropsychological, cognitive, social, and psychology. From their research it found that generally bilingualism is an asset and not a burden. The analysis is also supported by argument and some examples from bilingual peoples.